2012
DOI: 10.1111/j.1465-7295.2011.00430.x
|View full text |Cite
|
Sign up to set email alerts
|

On the Evolution of Total Factor Productivity in Latin America

Abstract: Because of several policy distortions, including import‐substitution industrialization, widespread government intervention, and both domestic and international competitive barriers, there has been a general presumption that Latin America has been much less productive than the leading economies in the last decades. In this paper we show, however, that until the late 1970s Latin American countries had high productivity levels relative to the United States. It is only after the late 1970s that we observe a fast d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 25 publications
3
26
0
2
Order By: Relevance
“…In contrast to the U.S. productivity, which has grown especially in high-productivity service activities, Brazilian labor productivity grew faster in labor-intensive sectors, such as agriculture and transport. Such findings meet those of Ferreira et al (2011), who similarly found divergent trend in American and Brazilian total factor productivity since early 1980s. Other authors (Cruz et al, 2007;Rocha, 2007) also mention the employment trend towards low-technology and low-productivity segments of the industry in the 1980s and 1990s, which may have persisted in the industry and service activities over the 2000s.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…In contrast to the U.S. productivity, which has grown especially in high-productivity service activities, Brazilian labor productivity grew faster in labor-intensive sectors, such as agriculture and transport. Such findings meet those of Ferreira et al (2011), who similarly found divergent trend in American and Brazilian total factor productivity since early 1980s. Other authors (Cruz et al, 2007;Rocha, 2007) also mention the employment trend towards low-technology and low-productivity segments of the industry in the 1980s and 1990s, which may have persisted in the industry and service activities over the 2000s.…”
Section: Discussionsupporting
confidence: 73%
“…Several factors that contribute to configure labor productivity can help explaining the low level of productivity in Brazil in comparison with the U.S. For instance, Restuccia (2009) highlights how Latin American countries have been characterized by institutions and policy distortions, such as high costs to start a business, barriers to formal market entry and different forms of regulations, which many times misallocated resources across plants and shifted the distribution of plants to lower productivity levels. The low level of investment in innovation and technology is another frequently mentioned factor influencing productivity in Brazil (ECLAC, 2010) as well as the level and quality of the working force education (Ferreira et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A contribuição da produtividade total dos fatores no Brasil, bem como no restante da América Latina, tem sido baixa em comparação com as economias desenvolvidas (Cole et al, 2005;Ferreira, 2012). A acumulação de capital no Brasil sempre foi viabilizada pela oferta abundante, "ilimitada", de mão de obra, de modo que o aumento de produção sempre pode ser acompanhado pelo aumento no número de horas trabalhadas sem causar-lhes maiores embaraços ou restrições.…”
Section: Mercado De Trabalho E Restrições De Oferta De Mounclassified